Can fishery subsidy improve fishermen’s income?——evidence from China’s coastal areas - Yujuan Li; Yujuan Li; Kim Hang Pham Do; Shamim Shakur; Xin Sun (Frontiers in Marine Science)
Numerous studies have demonstrated that fishery subsidies play a role in income redistribution, potentially contributing to economic inequality. Additionally, since fishermen are highly dependent on the marine environment, there may be a connection between marine pollution and their income levels. This study explores the effects of fishery subsidies and marine environmental pollution on fishermen’s income and income inequality using panel data from 11 coastal provinces and municipalities in China from 2006 to 2020. Applying panel fixed effect model and quantile regression models, the results show that fishery subsidies significantly increase income, but disproportionately benefit higher-income fishermen, thereby exacerbating income inequality. Moreover, the relationship between marine pollution and income is non-linear: moderate pollution is associated with income gains, while severe pollution reduces income. These findings suggest that subsidy policies should be better targeted, and stricter marine environmental regulation is necessary to protect vulnerable fishing communities